2020
DOI: 10.1039/d0cc00730g
|View full text |Cite
|
Sign up to set email alerts
|

NaH-mediated direct C–H arylation in the presence of 1,10-phenanthroline

Abstract: Transition-metal-free coupling of haloarenes with unactivated arenes has been developed in the presence of NaH and 1,10-phenanthroline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The number of charge transfer is likely related to the distinguished E bd and E int . Based on the geometries of M-based pyrrole compounds, the Na atom leans to bind H and likely forms the generally stable NaH. …”
Section: Resultsmentioning
confidence: 99%
“…The number of charge transfer is likely related to the distinguished E bd and E int . Based on the geometries of M-based pyrrole compounds, the Na atom leans to bind H and likely forms the generally stable NaH. …”
Section: Resultsmentioning
confidence: 99%
“…Arylation of haloarenes with unactivated heteroarenes under transition-metal-free conditions was reported in the presence of NaH and 1,10-phenanthroline by Nozawa-Kumada, Kondo, and co-workers (Scheme 29). 38 Crosscoupling reactions of various substituted haloarenes and nonactivated heteroarenes were easily performed with this arylation methodology. Mechanistic studies have shown a phenyl radical intermediate is formed through SET from the radical species generated by the reaction of NaH and 1,10phenanthroline.…”
Section: Arylation Of Heteroarenes With Pseudohalides or Aryl Halidesmentioning
confidence: 99%
“…[5] Recently, we reported the NaH-mediated coupling reaction of aryl halides with unactivated arenes in the presence of 1,10-phenanthroline. [6] This reaction proceeds via the addition of aryl radicals, formed through SET by NaH and 1,10-phenanthroline, to unactivated arenes (Scheme 1a). Regarding coupling reactions of aryl halides with alkenes, tert-butoxide salt-mediated Mizoroki-Heck type reactions with appropriate additives to afford stilbene derivatives have been reported (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…For reductants, the combination of strong bases and additives such as 1,10‐phenanthrolines, [4a,b] anilines, [4c,d] amines, [4e,f] and alcohols [4g,h] has attracted great attention over the past few decades, as electron donors can be easily generated in situ [5] . Recently, we reported the NaH‐mediated coupling reaction of aryl halides with unactivated arenes in the presence of 1,10‐phenanthroline [6] . This reaction proceeds via the addition of aryl radicals, formed through SET by NaH and 1,10‐phenanthroline, to unactivated arenes (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%